Relationship Between Generations of Entrepreneurs and Entrepreneurial Traits - Eken, Ihsan (Journal of Applied Business and Economics, 2018)
Quantitative descriptive study investigated the relationship between 3 different generations of entrepreneurs and entrepreneurship traits. The purpose of this study was to investigate the relationship between entrepreneurial traits and generations of U.S. entrepreneurs in Southwest, Northeast, Central, and Southeast Texas, to see whether generational differences are associated with entrepreneurial traits. 3 different generations of entrepreneurs were investigated in the study. The research aimed to contribute beneficial insights to their understanding in enterprising potential and differentiate themselves in entrepreneurial traits. GET2 test was used to collect the data to analyze the differences and similarities between generations of entrepreneurs and entrepreneurial traits.